2020
DOI: 10.1136/bmjebm-2020-111499
|View full text |Cite
|
Sign up to set email alerts
|

Quality of early evidence on the pathogenesis, diagnosis, prognosis and treatment of COVID-19

Abstract: Since the initial description of the SARS-CoV-2 outbreak and its declaration as a worldwide pandemic, the number of publications on the novel virus has increased rapidly. We studied the trends and quality of evidence in early SARS-CoV-2 publications. A comprehensive search of MEDLINE and EMBASE was performed for papers published between 1 January 2020 and 21 April 2020. Two reviewers independently screened titles and abstracts and subsequently full texts for eligibility in this systematic review. The search yi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Although many prognostic criteria have been proposed, a recent systematic review of literature yielded an urgent need for high‐quality diagnostic and prognostic data for COVID‐19 22 . The authors note that “Of 541 papers that reported clinical characteristics, 295 were commentaries/expert opinions and 36 were case reports.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although many prognostic criteria have been proposed, a recent systematic review of literature yielded an urgent need for high‐quality diagnostic and prognostic data for COVID‐19 22 . The authors note that “Of 541 papers that reported clinical characteristics, 295 were commentaries/expert opinions and 36 were case reports.…”
Section: Discussionmentioning
confidence: 99%
“…The authors note that “Of 541 papers that reported clinical characteristics, 295 were commentaries/expert opinions and 36 were case reports. There were no randomized clinical trials, 45 case series studies, 58 narrative reviews, 1 cohort study, and 5 systematic reviews.” 22 The RECOVER registry may be unique because it includes ED patients who are both SARS‐CoV‐2 positive, as well as those who had suspected COVID‐19, but who have negative diagnostic testing for SARS‐CoV‐2. This methodology specifically addresses the current critical need for a data set to derive and test–pretest probability and exclusionary rules for COVID‐19, as has been done with many other diseases, notably pulmonary embolism 23 .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the quality of the published work was not assessed in our analysis, but several evaluations raise concerns about many of the COVID-19 publications being of low quality. 1719 Massive productivity has been described in the pre-COVID era, as affecting researchers across many fields 20 and may be also a feature for COVID-19 research. Extreme productivity would be worrisome if it sacrifices quality.…”
Section: Discussionmentioning
confidence: 99%
“…quality appraised the studies using: Effective Public Health Practice Project (EPHPP) tool for interventional or observational study designs [ 10 ]; Newcastle–Ottawa scale for cohort studies [ 11 ]; Joanna Briggs Institute checklist for case series [ 12 ]; Scale for the Assessment of Narrative Review Articles (SANRA) scale for narrative reviews [ 13 ]; AMSTAR 2 critical appraisal tool for systematic reviews [ 14 ]; and an adapted version of the Consolidated Health Economic Evaluation Reporting Standards (CHEERS) checklist for modelling studies (with questions 1, 6, 8–14 and 19–21 omitted, as these were not relevant to non-economic modelling studies) [ 15 ]. In the absence of an appropriate standardized tool for appraisal of descriptive case studies, we documented key factors that were likely to influence study quality [ 16 , 17 ].…”
Section: Methodsmentioning
confidence: 99%